Pengukuran Volume Benda Padat Berbagai Bentuk dengan Berdasarkan Volume Desakan Pada Bahan Curah - B. Rahardjo; B. Suratmo; R. Kushendrati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1997)
Some of the standard methods to measure the solid volume are based on fluid displacement. However, most of agricultural products are absorbable to water and certain fluids. Therefore the use of fluids to determine the volume of agricultural products can cause error. Where as bulk materials on certain condition behave and flow such as fluids but are not absorbable to products. Accordingly the objectives of the research were to evaluate the accuracy of volume measurement of solid particles with several shapes using bulk materials and to determine the measurement error and its relation to the pertinent parameters. The volume determined using bulk materials were compared with that measured using standard methods. The errors of the measurements were related to the pertinent parameters such as granular size and solid particle size. Samples used were spheres, cylinders, cubes, prisms and any shapes of solid particles made from wood, glass, bronzes or stone with any shapes. The bulk material was sand found on rivers around the city of Yogyakarta. The results indicate that the particle volume can be determined using bulk materials. However, volume measured using bulk materials was higher than that determined using standard methods. The volume errors increases as the granular size increases and as the solid particle size decreases. The error can be related to the granular particle size ratio quite well. The corrected volume with the estimed error was closely similar to the volume determined using standard methods. Bulk materials consisting of small size, smooth surface and sphere like shape granules are likely ideal medium for solid volume measurements.